Competency Evaluation and Performance Training against Merdeka Belajar Curriculum among Kindergarten Teachers - Ariq Nurjannah Irbah; Ichsan Ichsan; Nurul Fauziah (JOYCED: Journal of Early Childhood Education, 2022)
After the pandemic, there have been various controversies in the world of education, namely that there are institutions that are ready or not for the Merdeka Belajar Curriculum. These considerations range from skill preparation and teacher training, to teacher performance. Teacher training activities are still few, and teaching skills are not paid attention to, so teacher performance is less than optimal. So it is very necessary for educational institutions to first evaluate the human resources of teachers, before taking the curriculum policy initiated by the Ministry of Education and Culture. Especially for Kindergarten institutions, which are a necessary basis for children's education. It is so important to study more deeply, so this study aims to determine the evaluation of teacher competence and performance training on the readiness of the Merdeka Belajar Curriculum at Kindergarten As Sa'adah Yogyakarta. Thee research method used is quantitative, with 12 kindergarten teachers as participants. While the data collection techniques with questionnaires, observation sheets, interviews, and documentation. The data analysis technique used quantitative descriptive analysis, namely collecting data, processing data, and describing the percentage of questionnaire answers from participants. The results showed that the Kindergarten As Sa'adah Yogyakarta teachers, from the aspect of competence (78%), and performance (77%) were ready for the implementation of the Merdeka Belajar Curriculum, but not yet ready for the training aspect (68%), and the readiness of the Merdeka Belajar Curriculum (72%). So that the implementation of the Merdeka Belajar Curriculum in Kindergarten As Sa'adah Yogyakarta must be reconsidered because teacher training is not yet mature.